Alternative Assessments: Performance Assessment, Authenticity, Portfolios and Methods of Implementing Performance Assessments / Pentaksiran Alternatif: Pentaksiran Prestasi, Autentik, Portfolio dan Kaedah Pelaksanaan Pentaksiran Prestasi - Said, Nurul Akmar (Sains Humanika, 2020)
Assessment is part of the teaching and learning process, aimed at improving student performance. Assessment also improves the quality of education, which enhances lifelong learning skills and performance in the educational context. Evaluation is a form of process of measuring the assessment process. It is a systematic process that involves the collection, analysis and translation of student achievement levels into the teaching objectives. Today, alternative assessments implemented in the learning system are a form of assessment that complements conventional assessment. Alternative assessments focus on student growth over time as well as the final process. And finally there are four categories of performance assessment namely response building, product evaluation, performance assessment and process focus assessment. Each category comes with examples of activities to help teachers teach and learn in the classroom